A retrospective study of 267 bilio-jejunal anastomosis: análisis de 267 casos - Estefan, Alberto; Beguiristaín, Alberto; Lago, Fernando; Berta, José; Cassinasco, Ángeles (Cirugía del Uruguay, 1983)
A retrospective study of 267 bilio yeyunal anastomosis is presented.